2002
DOI: 10.1191/1362168802lr096oa
|View full text |Cite
|
Sign up to set email alerts
|

Learners’ evaluations of teacher-fronted and student-centred classroom activities

Abstract: Various claims have been made in the educational literature about the relative merits of pair and group activities in classrooms. With the shift in language teaching towards a more learner-centred approach, however, there is now a stronger emphasis on the views of learners themselves. One hundred and three Brazilian EFL students (beginners, elementary, intermediate) completed and then evaluated different types of learning activities: teacher-fronted grammar (TFG), student-centred grammar (SCG), teacher-fronted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 18 publications
1
23
0
1
Order By: Relevance
“…For instance, Garrett and Shortall (2002) found that GW could achieve the following: increase the shared help between students; allow them to practise the language more; increase concentration in learners and their engagement with the interaction sitting; and reduce anxiety in language learners. According to a study by McDonough (2004), which investigated learner-learner interaction through pair and group work in a Thai EFL context, several students said that talking to others was helpful for them in learning English.…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
“…For instance, Garrett and Shortall (2002) found that GW could achieve the following: increase the shared help between students; allow them to practise the language more; increase concentration in learners and their engagement with the interaction sitting; and reduce anxiety in language learners. According to a study by McDonough (2004), which investigated learner-learner interaction through pair and group work in a Thai EFL context, several students said that talking to others was helpful for them in learning English.…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
“…What makes research into this area worthwhile for language pedagogy is the necessity of a relative match between the CF perceptions and preferences of students and teachers. Many studies have revealed the negative effects of a lack of such agreement on the process of language learning and teaching (Garrett & Shortall, 2002;Green, 1993;McCargar, 1993;Morris & Tarone, 2003;Noels, 2001;Noels, Clément, & Pelletier, 1999;Peacock, 2001;Reid, 1987;Terrell, 1977;Tse, 2000). According to Plonsky and Mills (2006) the mismatch between the views of the two groups may cause tension, demotivation, frustration, and other learning conditions which are detrimental to the goal of language learning.…”
Section: Introductionmentioning
confidence: 99%
“…As learner autonomy plays an important role in long life English learning and teaching, Duan (2005) suggested four effective ways including changing the beliefs of teachers and learners, teaching learning strategies, using cooperative learning, and taking advantage of computer resources to foster it. Garrett and Shortall (2002) investigated the relationships among enjoyment, anxiety, and learning value of 103 Brazilian EFL students at different proficiency levels: beginners, elementary, and intermediate with different types of classroom interaction: pair work and small group work and learning activities: teacher-fronted grammar (TFG), student-centered grammar (SCG), teacher-fronted fluency (TFG), and student-centered fluency (SCF). They concluded that there were significant differences among the students at different levels.…”
Section: Learner Autonomymentioning
confidence: 99%